Clitorodynia: A Descriptive Study of Clitoral Pain. (1st August 2015) - Parada, Mayte; D'Amours, Tanya; Amsel, Rhonda; Pink, Leah; Gordon, Allan; Binik, Yitzchak M.
ABSTRACT: Introduction: Clitorodynia is classified as a type of localized vulvodynia. Our knowledge of this problem is limited to case studies and one published report. Aims: The objective of the present study was to describe quantitatively the clinical characteristics of clitoral pain, to assess interference with sexual function, and to investigate whether clitoral pain is a unitary category. Methods: One hundred twenty‐six women with clitoral pain completed an online questionnaire that assessed demographic information, descriptive pain characteristics, intensity and impact on daily activities, sexual function, and gynecological and medical histories. Main Outcome Measures: The main outcome measures used for the study are the following: clitoral pain characteristics (e.g., intensity, duration, quality, distress, etc.), short‐form McGill pain questionnaire‐2, and the female sexual function index. Results: Clitoral pain is characterized by frequent and intense pain episodes that can either be provoked or unprovoked, and causes significant impairment in both daily and sexual function. The pain can be localized to the clitoris only or can occur with other genital pain. Comorbidity with other chronic pain disorders is common. A cluster analysis suggested two distinct patterns of clitoral pain, one localized and one generalized. Conclusion: Our findings indicate that women with clitoral pain suffer from significant, distressing, and often long‐term pain, which interferes with sexual and daily activities. Two subtypes of clitoral pain may exist, each with distinct pain characteristics and subjective experiences.